2012
DOI: 10.1128/aem.02144-12
|View full text |Cite
|
Sign up to set email alerts
|

Residual Viral and Bacterial Contamination of Surfaces after Cleaning and Disinfection

Abstract: c Environmental surfaces contaminated with pathogens can be sources of indirect transmission, and cleaning and disinfection are common interventions focused on reducing contamination levels. We determined the efficacy of cleaning and disinfection procedures for reducing contamination by noroviruses, rotavirus, poliovirus, parechovirus, adenovirus, influenza virus, Staphylococcus aureus, and Salmonella enterica from artificially contaminated stainless steel surfaces. After a single wipe with water, liquid soap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 57 publications
4
93
1
1
Order By: Relevance
“…Two studies published in 2012 found that norovirus (human and MNV1 strains) could be substantially reduced on hard surfaces after wiping from one to six times using a range of inocula and material wipes (121,149). This supports the increasingly popular premise that physical removal could challenge routine use of disinfectants for controlling surface microbes (163,164) (Fig.…”
Section: Benefits Of Physically Removing Soilsupporting
confidence: 48%
See 2 more Smart Citations
“…Two studies published in 2012 found that norovirus (human and MNV1 strains) could be substantially reduced on hard surfaces after wiping from one to six times using a range of inocula and material wipes (121,149). This supports the increasingly popular premise that physical removal could challenge routine use of disinfectants for controlling surface microbes (163,164) (Fig.…”
Section: Benefits Of Physically Removing Soilsupporting
confidence: 48%
“…Detergent-based cleaning is not sufficient to eliminate norovirus from the environment (120). A recent in vitro study measured residual contamination of surfaces with norovirus after detergent cleaning with or without a disinfectant (121). The authors concluded that cleaning with liquid soap followed by a 1,000-ppm chlorine wipe generally produced the lowest level of persistent contamination.…”
Section: Norovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…There are increasing reports that suggest physical, rather than biocidal, removal of bioburden is key to the cleaning process [50][51][52][53][54][55][56][57][58]. This is not necessarily due to the fact that surface soil is known to impede microbiocidal activity of a disinfectant [59].…”
Section: The Wiping Effectmentioning
confidence: 99%
“…A recent study by Tuladhar et al (46) demonstrated improved removal and inactivation of noroviruses by using wipes soaked in 250 ppm chlorine after the surfaces had been wiped once with soap and water, suggesting a two-step cleaning/sanitizing procedure should also be adopted to maximize the effectiveness of sanitizing wipes. Another note of importance revealed by this study was that, while a direct correlation between the removal of the MNV-1 surrogate and removal of human norovirus from surfaces via wiping was difficult to discern, in fact MNV-1 appears to be somewhat more susceptible to degradation by the mechanical action of wiping alone (46). Future studies should consider this potential limitation of the MNV-1 surrogate.…”
Section: Discussionmentioning
confidence: 97%